What does existing NeuroIS research focus on?. (March 2020) - Xiong, Jie; Zuo, Meiyun
Abstract: NeuroIS is a research field in which neuroscience theories and tools are used to better understand information systems phenomena. At present, NeuroIS is still an emerging field in information systems, and the number of available studies is limited. Because researchers who plan or execute NeuroIS research need to understand the status of the existing empirical research published in relevant journals, we have analyzed 78 empirical articles and put forward an integrative framework for understanding what existing NeuroIS research focuses on. Our framework is built upon stimulus–organism–response theory, which explains that stimulus factors can affect users' psychological processes, which further lead to their responses. Then, we review the collected articles and summarize their findings to give more details of NeuroIS studies. Through this literature review, we identify several opportunities for future NeuroIS research in terms of influencing factors, measurement instruments, and subjects. We believe that our work will provide some meaningful insight for future NeuroIS research. Highlights: A NeuroIS integrative framework is put forward to analyze existing NeuroIS research. NeuroIS studies focus on eight topics such as IS adoption and IS use efficiency. The main neuroscience tools might be used together in future NeuroIS research. Scholars should do more NeuroIS research on the elderly and other special groups.